Development of Arts Teacher Research Competence in Master Studies - Banevičiūtė, Birutė; Kudinovienė, Jolita (Pedagogika, 2017)
The problem of teachers’ research competence is one of the main aspects of concern in teacher education on master’s level. Arts teacher education is interdisciplinary studies which combine two areas – arts (music, dance, theatre, visual arts) and education, therefore research becomes a complex process requiring competence to use artistic expression forms and methods of social sciences research. In this article the point of view of arts education master’s students on research competence development is revealed.